Korelasi Tuhan dalam Pandangan Aristoteles dengan Konsep Satataning Panembah - Andini, Agni Dhea; Widayat, Afendy (Jurnal Dinamika Sosial Budaya, 2023)
The will of the first Mover, who is none other than God, is inextricably linked to the existence of people and everything else in the cosmos. God is the reason why everything has a purpose, including humans. Aristotle, a philosopher, held this philosophical idea to be true. The Javanese, on the other hand, have their own ideas on how to worship God as the architect of the universe. This approach, known as satataning panembah, includes sembah catur or four different forms of worship. Serat Wedhatama by KGPAA Mangkunegara IV contains sembah catur. The goal of qualitative descriptive research is to identify the connections between the two, notably Aristotle's conception of God and the idea of satataning panembah, through gathering evidence through literary study. The study's findings indicate a connection between God and the four forms of worship practiced by the Javanese people it s sembah raga, sembah cipta, sembah jiwa, and sembah rasa according to Aristotle. The connection is that there is a means to reach human unity with God, which is the height of human perfection.